2007
DOI: 10.2987/8756-971x(2007)23[335:neotma]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Nontarget Effects of the Mosquito Adulticide Pyrethrin Applied Aerially During a West Nile Virus Outbreak in an Urban California Environment

Abstract: In August 2006, a pyrethrin insecticide synergized with piperonyl butoxide (EverGreenH Crop Protection EC 60-6, McLaughlin Gormley King Company, Golden Valley, MN) was sprayed in ultralow volumes over the city of Davis, CA, by the Sacramento-Yolo Mosquito and Vector Control District to control mosquitoes transmitting West Nile virus. Concurrently, we evaluated the impact of the insecticide on nontarget arthropods by 1) comparing mortality of treatment and control groups of sentinel arthropods, and 2) measuring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 6 publications
3
36
1
Order By: Relevance
“…The results for permethrin are different from those of Tietze et al (1996), who found that ULV applications of malathion caused significant mortality of sentinel crickets. However, the results of our study are supported by Davis and Peterson (2008), Kwan et al (2009), Boyce et al (2007, and Hill et al (1971), showing little to no impact on medium-to large-bodied common terrestrial arthropods after single and multiple ULV applications.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…The results for permethrin are different from those of Tietze et al (1996), who found that ULV applications of malathion caused significant mortality of sentinel crickets. However, the results of our study are supported by Davis and Peterson (2008), Kwan et al (2009), Boyce et al (2007, and Hill et al (1971), showing little to no impact on medium-to large-bodied common terrestrial arthropods after single and multiple ULV applications.…”
Section: Discussionsupporting
confidence: 55%
“…The risks to medium and large-bodied insects after aerial applications are most likely lower than those estimated here because concentrations deposited on the ground are generally lower than truck-mounted ULV applications (Schleier III et al 2008), which is supported by Boyce et al (2007) and Kwan et al (2009) who observed no significant mortality of these size classes after aerial applications of synergized pyrethrins. The results for permethrin are different from those of Tietze et al (1996), who found that ULV applications of malathion caused significant mortality of sentinel crickets.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…Other studies of mosquito control impacts have had similar results to ours. For example, Boyce et al (2007) saw no effect on caged sentinel insects (dragonßies, spider, butterßies, and honey bees) but found some small-bodied insects declined after sprays. Likewise, Davis and Peterson (2008) found few impacts of pyrethroid sprays on terrestrial nontarget insects.…”
Section: Discussionmentioning
confidence: 96%
“…For example, avian breeding in salt marshes could be impacted if invertebrates decline when juveniles are feeding. Conversely, mosquito control could beneÞt birds by reducing arbovirus transmission within their populations (Boyce et al 2007). This suggests that there might be both positive and negative ecological effects if spray impacts are consistent and large enough to affect ecosystem processes.…”
Section: Discussionmentioning
confidence: 98%